When a polyester mesh causes an enterocutaneous fistula, 30 years after its implantation - Mohamed Farès Mahjoubi; Nada Essid; Bochra Rezgui; Mohamed Zran; Karim Haouet; Mounir Ben Moussa (Clinical Case Reports, 2022)
Abstract Digestive fistula on mesh is an exceptional and late complication of hernioplasty. The type of mesh and its position are often implicated in its occurrence. Clinical presentation is multiform. Morphological examinations are essential to confirm the diagnosis, and the curative treatment remains surgical.